Language Proficiency as A Social Capital among Indonesian Migrant Workers: from Language Acquisition to Language Maintenance - Diding Fahrudin (Universitas Bunda Mulia, 2017)
The economic and social pressure has led many Indonesian to become migrant workers in some foreign countries for a better life. Their poor language proficiency due to their lack of preparation prior to their departure has hampered them from communicating well in the country of destination which they have lived. This paper presents the analysis of how the Indonesian migrant workers prepared their language proficiency in their country of origin,Indonesia, how they have acquired the language of the receiving country in which they have worked, and how they have maintained the acquired foreign language upon their return toIndonesiaas their social capital. This paper found out that language preparation, language acquisition and language maintenance play very important roles in the life of Indonesian migrant workers. Poorly planned language training has made the migrant workers face many problems in communication in the country of destination. This condition can be gradually solved by acquiring the language during their work in the country of destination and this language acquisition through immersion has become their social capital; however, such social capital is not well processed to empower the community in most areas of the country of origin,Indonesia. This fact is worsened by the reality that the formal government structure in the villages seems to neglect this self-empowered group of the community. Key words: Economic and social pressure, migrant workers, proficiency, acquired, social capital